2021
DOI: 10.1002/jcla.23687
|View full text |Cite
|
Sign up to set email alerts
|

Expression profile of circular RNAs in cystic echinococcosis pericystic tissue

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Differentially expressed miRNAs (miR-181, miR-30, miR-365, miR-378, miR-449, and miR-16) that were identified in the sheep intestine, liver, and serum, as well as in mouse macrophages, following infection with E. granulosus may be critically involved in the body's immune response [ 30 32 ]. Microarray analysis of circRNA expression profiles in adjacent tissues of CE-infected patients showed that hsa_circRNA_006773, hsa_circRNA_049637, hsa_circRNA_104349, and hsa_circRNA_406281 might serve as CE prognostic biomarkers and therapeutic targets [ 33 ]. Interestingly, lncRNA regulates lipolysis and metabolic remodeling in E. granulosus –infected mice [ 34 ].…”
Section: Analysis and Discussion Of Clinical Datamentioning
confidence: 99%
“…Differentially expressed miRNAs (miR-181, miR-30, miR-365, miR-378, miR-449, and miR-16) that were identified in the sheep intestine, liver, and serum, as well as in mouse macrophages, following infection with E. granulosus may be critically involved in the body's immune response [ 30 32 ]. Microarray analysis of circRNA expression profiles in adjacent tissues of CE-infected patients showed that hsa_circRNA_006773, hsa_circRNA_049637, hsa_circRNA_104349, and hsa_circRNA_406281 might serve as CE prognostic biomarkers and therapeutic targets [ 33 ]. Interestingly, lncRNA regulates lipolysis and metabolic remodeling in E. granulosus –infected mice [ 34 ].…”
Section: Analysis and Discussion Of Clinical Datamentioning
confidence: 99%
“…Differentially expressed miRNAs (miR-181, miR-30, miR-365, miR-378, miR-449, miR-99, miR-130, and miR-16) that were identi ed in the sheep intestine, liver, and serum, as well as in mouse macrophages, following infection with E. granulosus may be critically involved in the body's immune response [29][30][31][32][33][34][35][36][37][38][39] . Microarray analysis of circRNA expression pro les in adjacent tissues of CE-infected patients, showed that hsa_circRNA_006773, hsa_circRNA_049637, hsa_circRNA_104349, and hsa_circRNA_406281 might serve as CE prognostic biomarkers and therapeutic targets [40] . Our high-throughput sequencing data are consistent with previous results showing that miR-29c-3p and miR-30b-5p are signi cantly downregulated in CE [41] .…”
Section: Discussionmentioning
confidence: 99%
“…Microarray analysis is a sensitive tool to accurately investigate differentially expressed circRNAs during many disease processes [4][5][6][7][8]. It is based on hybridization and fluorescence detection and uses specific probes targeting the back-spliced junction of each circRNA.…”
Section: To the Editormentioning
confidence: 99%